2010
DOI: 10.1111/j.1469-7998.2010.00778.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographical origin and endemism of Corsican Kuhl's pipistrelles assessed from mitochondrial DNA

Abstract: Previous genetic analyses have demonstrated that two divergent lineages of Pipistrellus kuhlii are spread over Europe and North Africa, and it has been proposed that Pipistrellus maderensis, a taxon endemic to the Canary Archipelago and Madeira, was its sister species. In this study, we used mitochondrial DNA sequences to investigate the level of endemism achieved by Corsican lineages with regard to their continental counterparts and to propose hypotheses about the geographical origin of Corsican bats. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
3
8
0
Order By: Relevance
“…As already documented in all reconstructions based on distinct mitochondrial genes (e.g., Ibáñez et al 2006, Mayer et al 2007, Evin et al 2011, Veith et al 2011, Çoraman et al 2013, sequences issued from this species complex form more or less wellseparated clades, but relationships among them lack resolution, which is fully consistent with the reconstructions presented in Figure 7.…”
Section: Genetic Comparisonsupporting
confidence: 77%
“…As already documented in all reconstructions based on distinct mitochondrial genes (e.g., Ibáñez et al 2006, Mayer et al 2007, Evin et al 2011, Veith et al 2011, Çoraman et al 2013, sequences issued from this species complex form more or less wellseparated clades, but relationships among them lack resolution, which is fully consistent with the reconstructions presented in Figure 7.…”
Section: Genetic Comparisonsupporting
confidence: 77%
“…kuhlii sensu stricto and rendering the latter taxon paraphyletic (e.g. [ 14 , 15 , 16 ]). The genetic divergence between the main lineages in this complex is ca.…”
Section: Introductionmentioning
confidence: 99%
“…co-occur in large parts of Western Europe [ 17 21 ], including Corsica [ 15 ] ( Fig 1 ). Individuals from both lineages have also been found in Northern Italy [ 15 ] near the type locality of P . kuhlii s .…”
Section: Introductionmentioning
confidence: 99%
“…A North African origin has also been shown for P. pygmaeus (Hulva et al. , 2010), whereas a European origin has been reported for P. kuhlii (Evin et al. , 2011).…”
Section: Discussionmentioning
confidence: 88%
“…In M. punicus, both phenotypic similarity (Evin et al, 2008) and molecular phylogenetics (Castella et al, 2000) have demonstrated closer relationships between the Corsican and North African populations than between those populations and populations from other parts of the species' distribution. A North African origin has also been shown for P. pygmaeus (Hulva et al, 2010), whereas a European origin has been reported for P. kuhlii (Evin et al, 2011). In the case of P. pipistrellus, the Corsican population shows greater phenotypic similarity with the northern lineages of P. pipistrellus pipistrellus and P. pipistrellus aladdin than with the Moroccan lineage.…”
Section: Diversification Patternsmentioning
confidence: 83%